Impact of KvLQT1 potassium channel modulation on alveolar fluid homeostasis in an animal model of thiourea-induced lung edema - Aubin Vega, Mélissa; Girault, Alban; Adam, Damien; Chebli, Jasmine; Privé, Anik; Maillé, Émilie; Robichaud, Annette; Brochiero, Emmanuelle (Frontiers in Physiology, 2023)
Alveolar ion and fluid absorption is essential for lung homeostasis in healthy conditions as well as for the resorption of lung edema, a key feature of acute respiratory distress syndrome. Liquid absorption is driven by active transepithelial sodium transport, through apical ENaC Na+ channels and basolateral Na+/K+-ATPase. Our previous work unveiled that KvLQT1 K+ channels also participate in the control of Na+/liquid absorption in alveolar epithelial cells. Our aim was to further investigate the function of KvLQT1 channels and their interplay with other channels/transporters involved in ion/liquid transport in vivo using adult wild-type (WT) and KvLQT1 knock-out (KO) mice under physiological conditions and after thiourea-induced lung edema. A slight but significant increase in water lung content (WLC) was observed in naïve KvLQT1-KO mice, relative to WT littermates, whereas lung function was generally preserved and histological structure unaltered. Following thiourea-induced lung edema, KvLQT1-KO did not worsen WLC or lung function. Similarly, lung edema was not aggravated by the administration of a KvLQT1 inhibitor (chromanol). However, KvLQT1 activation (R-L3) significantly reduced WLC in thiourea-challenged WT mice. The benefits of R-L3 were prevented in KO or chromanol-treated WT mice. Furthermore, R-L3 treatment had no effect on thiourea-induced endothelial barrier alteration but restored or enhanced the levels of epithelial alveolar AQP5, Na+/K+-ATPase, and ENaC expressions. Altogether, the results indicate the benefits of KvLQT1 activation in the resolution of lung edema, probably through the observed up-regulation of epithelial alveolar channels/transporters involved in ion/water transport.